Teor de metais pesados em alface (Lactuca saliva L.) adubada com composto orgânico de lixo urbano - DA COSTA, CÂNDIDO ALVES; CASALI, VICENTE WAGNER DIAS; LOURDES, EMÍLIO GOMIDE; CECON, PAULO ROBERTO; JORDÃO, CLAUDIO PEREIRA (Revista Ceres, 2015)
.